Energy Consumption and Generation Diversity - Harnphattananusorn, Supanee; Puttitanun, Thitima (International Journal of Energy Economics and Policy, 2022)
This study investigates whether generation diversity in population can influence energy consumption. Using a panel data of 37 OECD countries over the years 1980-2021, it is found that apart from the size of population by age, generation diversity can influence the electric consumption per head of OECD countries. Specifically, an increase in generation diversity decreases the electric consumption. High generation diversity can lead to a smaller household, where energy consumption can be more efficiently managed. High generation diversity can also lead to high income variation that results in diversity in energy source consumption. Moreover, younger generations, concerning over environmental issues and energy conservation, can influence older generations to conserve more energy through bandwagon effect. This study shows that generation diversity is an important dimension in population structure that can influence electricity consumption. Hence, generation diversity needs to be considered in planning for energy management strategies.